Interactions between the oomycete Pythium arrhenomanes and the rice root-knot nematode Meloidogyne graminicola in aerobic Asian rice varieties - Verbeek, R. E. M.; Banaay, C. G. B.; Sikder, M.; De Waele, D.; Vera Cruz, C.M.; Gheysen, G.; Höfte, M.; Kyndt, Tina (Springer, 2016)
Aerobic rice fields are frequently infested by pathogenic oomycetes (Pythium spp.) and the rice root-knot nematode Meloidogyne graminicola. Here, the interaction between Pythium arrhenomanes and Meloidogyne graminicola was studied in rice roots of two aerobic rice varieties. In different experimental set-ups and infection regimes, plant growth, rice yield, Pythium colonization, as well as establishment, development and reproduction of M. graminicola were studied. In this study, it is shown that the presence of P. arrhenomanes delays the establishment, development and reproduction of M. graminicola compared to single nematode infected plants. The delay in establishment and development of M. graminicola becomes stronger with higher P. arrhenomanes infection pressure. Our data indicate that P. arrhenomanes antagonizes M. graminicola in the rice root and that the plant benefits from this antagonism as shown by the yield data, especially when either of the pathogens is present in high levels